The methods I used and the roles I played in teaching reading to standard 3 and 4 at BIAM laboratory school - Sharmin, Rumana (BRAC University, 2013)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2013.